Satisfactory levels of functionality and quality of life in caregivers of patients with bipolar disorder: is this possible? - Mariana Troesch; Sarah Prates; Stella Sarmento; Thiago Cerqueira-Silva; Gabriela Léda-Rêgo; Caroline Dallalana; Juliana S. Casqueiro; Paula Studart-Bottó; Ângela Miranda-Scippa (Brazilian Journal of Psychiatry)
Objective: Functionality and quality of life levels were measured in caregivers of patients with bipolar disorder, investigating the associations between them and with clinical and sociodemographic data. Method: A cross-sectional study was conducted between 2020 and 2022 with caregivers of patients with bipolar disorder treated in a university hospital’s outpatient clinic. The following instruments were applied: a clinical and sociodemographic questionnaire, the World Health Organization Disability Assessment Schedule 2.0, the 36-Item Short Form Health Survey, the Mini International Neuropsychiatric Interview Plus, and the Structured Clinical Interview for DSM-IV Axis II Personality Disorders. Results: The median World Health Organization Disability Assessment Schedule 2.0 score was < 20, and the median score on the 36-Item Short Form Health Survey domains was > 60. Caregivers with greater functional impairment had lower quality of life. Being younger, being a parent, having non-psychiatric clinical conditions, and having mental disorders were associated with lower quality of life and functionality. Conclusion: These results indicate less functional impairment and better perceived quality of life than what has been reported in the literature, demonstrating that there is a subgroup of caregivers who perform their role without significant compromise to these health aspects. Exploring other factors associated with functionality and quality of life, such as resilience, psychological support, etc., may allow for more targeted public health interventions, optimizing comprehensive bidirectional care for patients and caregivers.